Pemberdayaan Masyarakat Desa Girilaya Melalui Pelatihan Olahan Singkong dan Penguatan Ekonomi Kreatif Desa Girilaya - Dewi Rahmahwati; Vera Mulyawantie; Muhammad Gibran Hizbullah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Cassava is a local food commodity with significant potential to support food security and strengthen the rural community economy. However, the utilization of cassava in Girilaya Village remains limited to simple processed products, resulting in suboptimal economic value added. This community service activity aims to enhance community skills in processing cassava into value-added products while strengthening the managerial capacity of village-based Micro, Small, and Medium Enterprises (MSMEs). The implementation method employed a descriptive qualitative approach through several stages, including preparation, educational seminars, practical demonstrations of cassava processing, and activity evaluation. The activity involved 15 participants, including MSME actors, members of the Family Welfare Movement (PKK), and residents of Girilaya Village. The results indicate an improvement in participants’ knowledge and skills in diversifying processed cassava products, such as kodehel, opak beca, and cassava croquettes, as well as enhanced understanding of branding, marketing, and business legality. This activity contributes to strengthening the village's creative economy through the optimization of cassava utilization as a local flagship commodity.